Transfer Pricing and Tax Avoidance on Profitability Through Thin Capitalization - Dasman, Sunita; Redi, Aurelius; Sulistyorini, Dian; Triwibowo, Edi (LPPM Universitas Pelita Bangsa, 2024)
Palm oil is the most important plantation product because it has a high value compared to other plantation products and is also one of the main sources of exchange rates from other countries. Taxes are corporate obligations paid to the government for profits obtained by companies. Tax avoidance is to reduce taxes but still comply with tax regulations and laws. Profitability is the lifeblood of a company's management. This study aims to examine tax avoidance and thin transfer pricing on profitability mediated by thin capitalization using multiple linear regression and path analysis. The population in this study is oil palm plantation companies listed on the Indonesia Stock Exchange for the period 2018 – 2023. Transfer pricing does not affect profitability directly, but the presence of thin capitalization mediating factors can affect profitability. Meanwhile, tax avoidance does not affect thin capitalization or profitability.